¿Un packto patriarcal?: Normas de género y violencia sexual facilitada por tecnología en relaciones sexoafectivas de jóvenes universitarios/as en Lima (Perú) - Sarmiento Viena, Xinthya Katherine (2024)
Technology-facilitated sexual violence is a serious and prevalent issue in the digital era, particularly affecting the young population. A crucial but under-researched area where this form of violence manifests is in sexual-affective relationships. Digital technologies today permeate these interactions in various ways, creating an environment where gender-based violence takes on a particular complexity. Characteristics inherent to digital platforms, such as anonymity, virality, and digital permanence, exacerbate the impacts on victims. This research seeks to explain how gender norms influence the perceptions and experiences of technology facilitated sexual violence in the sexual-affective relationships of a group of young students at a public university in Lima, Peru. A qualitative methodology is used, based on in-depth interviews with male and female university students, as well as observations in campus meeting spaces. Five main forms of technology-facilitated sexual violence are identified: cyber exhibitionism, coercive sexting, spreading sexual rumors about the partner, non-consensual dissemination of intimate content, and exposing the partner or ex-partner to cybersexual harassment. It is argued that gender norms function as frames of reference that young people use to make sense of their experiences of technology-facilitated sexual violence, whether in their role as victims, perpetrators, or witnesses, and decide how to cope with them.